2014
DOI: 10.1371/journal.pone.0111393
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Agents of Central Nervous System Infections among Febrile Hospitalized Patients in the Country of Georgia

Abstract: ObjectivesThere is a large spectrum of viral, bacterial, fungal, and prion pathogens that cause central nervous system (CNS) infections. As such, identification of the etiological agent requires multiple laboratory tests and accurate diagnosis requires clinical and epidemiological information. This hospital-based study aimed to determine the main causes of acute meningitis and encephalitis and enhance laboratory capacity for CNS infection diagnosis.MethodsChildren and adults patients clinically diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
2
20
1
2
Order By: Relevance
“…A similar study conducted in Bonn University Hospital, Bonn, Germany, reported a prevalence of 0.3% for HSV . Other studies reported a prevalence of 1.5% for HSV1 in Korea and 1.4% in Georgia . HSV1 was also reported in 3.4% and 6.5% in two studies conducted in adults living in Vietnam .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A similar study conducted in Bonn University Hospital, Bonn, Germany, reported a prevalence of 0.3% for HSV . Other studies reported a prevalence of 1.5% for HSV1 in Korea and 1.4% in Georgia . HSV1 was also reported in 3.4% and 6.5% in two studies conducted in adults living in Vietnam .…”
Section: Discussionmentioning
confidence: 73%
“…38 Other studies reported a prevalence of 1.5% for HSV1 in Korea 39 and 1.4% in Georgia. 40 HSV1 was also reported in 3.4% and 6.5%…”
Section: Ta B L E 1 Description Of Primers and Probesmentioning
confidence: 95%
“…PCR gibi amplifikasyon temelli yöntemlerle, viral nükleik asidin BOS'da saptanması, SSS enfeksiyonlarının tanısında önemli bir dönüm noktası olmuş ve böylece viral etkenleri belirlemedeki başarı %20-30'lardan, günümüzde %50-70'lere ulaşmıştır (8) . BOS'da PCR yöntemiyle etken arama, HSV, CMV ve enteroviral menenjit tanısı için önerilen tanı yöntemidir (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . HSV menenjitleri, viral menenjitlerin %1-3'ünü oluşturur.…”
Section: Discussionunclassified
“…Erken tanı ve tedavinin son derece önemli olduğu bu hastalıkta menenjit bulguları ile gelen olgular hızla değerlendirilmeli ve hemen uygun antimikrobiyal tedavi başlanmalıdır. Bu sayede ölüm oranını azaltmak ve komplikasyonsuz iyileşmeyi artırmak olası olmaktadır (13,14) . Bakteriyel menenjit şüphesi olan hastada rutin tanı koyma yöntemi, BOS Gram boyama ve BOS kültürü-dür.…”
Section: Introductionunclassified
“…Despite a recent publication in Georgia suggesting that this virus may be an etiologic agent for central nervous system infections, no published data are available on the burden of TBEV in Georgia. 24 The presence of the tick vector, however, is documented in the southern Caucasus. 25 Accordingly, our risk factor analysis identified tick bites as a risk factor for TBEV.…”
Section: Discussionmentioning
confidence: 99%